2013
DOI: 10.1124/dmd.113.054817
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Role of Metabolic Activation in Tyrosine Kinase Inhibitor–Dependent Hepatotoxicity: Induction of CYP3A4 Enhances the Cytotoxicity of Lapatinib in HepaRG Cells

Abstract: Idiosyncratic hepatotoxicity has been associated with the oral tyrosine kinase inhibitor lapatinib, which is used in metastatic breast cancer therapy. Lapatinib is extensively metabolized by cytochrome P450 3A4/5 to yield an O-debenzylated metabolite, which can undergo further oxidation to a reactive quinone imine. A recent clinical study reported that concomitant use of lapatinib with dexamethasone increased the incidence of hepatotoxicity in metastatic breast cancer patients treated with lapatinib, and so we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 30 publications
5
54
0
Order By: Relevance
“…In addition, Teo et al (2012) demonstrated that concurrent use of lapatinib with dexamethasone (CYP3A4 inducer) in metastatic breast cancer patients increased the risk of lapatinib-induced hepatotoxicity, suggesting the involvement of CYP3A-mediated bioactivation. We have previously shown that LAP-OH was more cytotoxic than lapatinib itself in the HepaRG hepatic cell model (Hardy et al, 2014). CYP3A4 induction by dexamethasone and rifampin potentiated lapatinib-induced cytotoxicity, which was correlated with increased formation of LAP-OH and reactive quinoneimine-cysteine conjugates (Hardy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Teo et al (2012) demonstrated that concurrent use of lapatinib with dexamethasone (CYP3A4 inducer) in metastatic breast cancer patients increased the risk of lapatinib-induced hepatotoxicity, suggesting the involvement of CYP3A-mediated bioactivation. We have previously shown that LAP-OH was more cytotoxic than lapatinib itself in the HepaRG hepatic cell model (Hardy et al, 2014). CYP3A4 induction by dexamethasone and rifampin potentiated lapatinib-induced cytotoxicity, which was correlated with increased formation of LAP-OH and reactive quinoneimine-cysteine conjugates (Hardy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that LAP-OH was more cytotoxic than lapatinib itself in the HepaRG hepatic cell model (Hardy et al, 2014). CYP3A4 induction by dexamethasone and rifampin potentiated lapatinib-induced cytotoxicity, which was correlated with increased formation of LAP-OH and reactive quinoneimine-cysteine conjugates (Hardy et al, 2014). More recently, Cameron and colleagues showed that O-dealkylated lapatinib induced mitochondrial stress and activation of the oxidative stress responsive transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) in HepG2 cells (Eno et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably attributed to an increase in bioactivation of the drug ( Figure 11A) due to induction of P450 3A4. The effect of induction on toxicity of lapatinib was recently demonstrated by Hardy et al (2014) who showed that induction of P450 3A4 by dexamethasone or rifampicin in HepaRG cells markedly enhanced the cytotoxicity of lapatinib. This correlated with increased formation of GSH adducts of the drug (Hardy et al, 2014).…”
Section: Influence Of Competing Pathways On Body Burden Of Reactive Mmentioning
confidence: 94%
“…The effect of induction on toxicity of lapatinib was recently demonstrated by Hardy et al (2014) who showed that induction of P450 3A4 by dexamethasone or rifampicin in HepaRG cells markedly enhanced the cytotoxicity of lapatinib. This correlated with increased formation of GSH adducts of the drug (Hardy et al, 2014). Similarly, induction of P450 3A, which is the predominant catalyst of the activation of troglitazone in humans, is probably associated with an increased bioactivation of the drug (Tettey et al, 2001).…”
Section: Influence Of Competing Pathways On Body Burden Of Reactive Mmentioning
confidence: 94%